2014
DOI: 10.1097/mpa.0000000000000088
|View full text |Cite
|
Sign up to set email alerts
|

The RON Receptor Tyrosine Kinase in Pancreatic Cancer Pathogenesis and Its Potential Implications for Future Targeted Therapies

Abstract: Pancreatic cancer remains a devastating disease with a mortality rate that has not changed substantially in decades. Novel therapies are therefore desperately needed. The RON receptor tyrosine kinase has been identified as an important mediator of KRAS oncogene addiction and is over-expressed in the majority of pancreatic cancers. Preclinical studies that inhibition of RON function decrease pancreatic cancer cell migration, invasion and survival and can sensitize pancreatic cancer cells to chemotherapy. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 81 publications
(85 reference statements)
0
21
0
Order By: Relevance
“…Overexpression of these systems has been observed in various cancers, including pancreatic cancer [13, 14]. Previous studies have demonstrated that HGF and MSP can induce pancreatic cancer cell proliferation, promote invasive phenotypes, and contribute to the progression of the disease [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of these systems has been observed in various cancers, including pancreatic cancer [13, 14]. Previous studies have demonstrated that HGF and MSP can induce pancreatic cancer cell proliferation, promote invasive phenotypes, and contribute to the progression of the disease [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the replacement of the amido group in compound 4 by a double bond as in compound 12 was beneficial in restoring the inhibition of the RON enzymatic activity at the expense of c-Met. The saturation of the double bond as in [7,5]-bicyclic compound 20 improves slightly the activity for RON, but c-Met as well. Likewise, the presence of a more compact [6,5]-bicyclic system 21 seems to have a better affinity for both RON and c-Met kinase domains by slightly shifting the orientation of both the lactam carbonyl and the phenyl substituent on the pyrazole ring.…”
Section: Introductionmentioning
confidence: 91%
“…The saturation of the double bond as in [7,5]-bicyclic compound 20 improves slightly the activity for RON, but c-Met as well. Likewise, the presence of a more compact [6,5]-bicyclic system 21 seems to have a better affinity for both RON and c-Met kinase domains by slightly shifting the orientation of both the lactam carbonyl and the phenyl substituent on the pyrazole ring. Thus, in order to maintain good selectivity for RON over c-Met, it is preferable to further explore the [7,5]-bicyclic system by adding more decorations on this part of the molecule that would allow us to increase the inhibitory activity for RON.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Research into RON in pancreatic cancer is a relatively recent development. The currently available evidence to support the potential role of RON in carcinogenesis of pancreatic cancer and implications for future targeted therapy in treating pancreatic cancer was previously reviewed (11). RON has been demonstrated to serve important roles in pancreatic cancer carcinogenesis (12)(13)(14), epithelial-mesenchymal transition (15,16), tumor migration (17)(18)(19), angiogenesis (20,21), cancer stem cells (22) and apoptotic resistance (14,23,24) as a part of the progression of pancreatic cancer, suggesting that RON may be a potential therapeutic target in the treatment of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%